ANALISIS VEGETASI GULMA PADA LADANG BROCCOLI (Brassica oleraceae var.italica l) DI KEBUN PENDIDIKAN UNIVERSITAS QUALITY BERASTAGI - Donatus Dahang (Universitas Quality, 2018)
An appropriate weed control is one of determining factors of agriculture crops growing. Effective of weeds control technics be dependent on kinds of crops and the weeds. The research of weeds vegetation analyses of cabbages unit land had been carried out in Education Farming Land of Universitas Quality Berastagi for three months, March to May 2017. The quadrangular method was used, by accounting the densities, dominances, frequencies, and important index value each of the weeds. Identification of weeds was done by using plants’ key determination guidance, by comparing the weeds that was discovered in the research location and the guidance, as well as the identically pictures of the weeds in certain references. Results of the research shown, there are 7 weeds were found, kentangan, grintingan, Goletrak beuti (Richardia brasiliensis Gomez), bebandotan (Ageratum conyzoides L), padang teguh (Themede arguens L. Hack), and ubi jalar (ipomea sp). The highest value of SDR (Summed Dominance Ratio) was Grintingan (28%) and the lowest was goletrak beuti (4.7%)